Evaluation of a mental health drop-in centre offering brief transdiagnostic psychological assessment and treatment for children and adolescents with long-term physical conditions and their families: a single-arm, open, non-randomised trial. Issue 1 (26th November 2020) - Catanzano, Matteo; Bennett, Sophie D; Kerry, Ellie; Liang, Holan; Heyman, Isobel; Coughtrey, Anna E; Fifield, Kate; Taylor, Chloe; Dalgleish, Tim; Xu, Laila; Shafran, Roz
Abstract : Background: Children and young people with long-term physical conditions have significantly elevated mental health needs. Transdiagnostic, brief psychological interventions have the potential to increase access to evidence-based psychological treatments for patients who attend health services primarily for physical health needs. Objective: A non-randomised study was conducted to assess the impact of brief, transdiagnostic psychological interventions in children and young people presenting at a drop-in mental health centre in the reception area of a paediatric hospital. Methods: 186 participants attending a transdiagnostic mental health drop-in centre were allocated to assessment and psychological intervention based on a clinical decision-making algorithm. Interventions included signposting, guided self-help based on a modular psychological treatment and referral to the hospital's paediatric psychology service. The primary transdiagnostic mental health outcome measure was the parent-reported Strengths and Difficulties Questionnaire (SDQ), which was given at baseline and 6 months post-baseline. Findings: There was a significant positive impact of attending the drop-in mental health centre on the SDQ (Cohen's d=0.22) and on the secondary outcome measure of Paediatric Quality of life (Cohen's d=0.55). Conclusions: A mental health drop-in centre offering brief, transdiagnostic assessment and treatment may reduce emotional and behavioural symptoms and improve quality of life in children and young people with mental health needs in the context of long-term physical conditions. A randomised controlled trial to investigate the specificity of any effects is warranted. Clinical implications: Drop-in centres for mental health needs may increase access and have beneficial effects for children and young people with physical conditions.